Belajar Sawit: Sebuah Platform Edukasi Digital Masa Depan Khusus untuk Petani Sawit dan Stakeholder Melalui Pendekatan Blanded Learning - Yulianto, Apri; Dewi, Della Kartika Anggita; Nurmansyah, Dimas (EXERO : Journal of Research in Business and Economics, 2023)
In order to achieve high productivity, especially for people-owned oil palm plantations, farmers need to have knowledge and skills through learning or guidance from oil palm experts. The objectives to be achieved from this study include: designing the Belajar Sawit application that makes it easier for farmers and prospective oil palm farmers to get updated information from oil palm experts, analyzing usability engineering and analyzing the responses of farmers and prospective oil palm farmers to the benefits of the Belajar Sawit application. The method used to analyze the technical aspects (usability) consists of field observation (direct observation), questionnaire and thinking aloud. Referring to the functional readiness of the Belajar Palm application, it is necessary to test several aspects, in the form of aspects: learnability, efficiency, memorability, errors, and (satisfaction) which are used to assess Belajar Sawit from user responses through questionnaires. This research has succeeded in designing the Belajar Palm website and application, with the main menu: Independent Learning, Training, Expertise, Counseling and Certification. The Palm Oil Learning Menu on: Certification and Training is the fastest menu found by respondents. Based on the evaluation of the usability of the Palm Oil Learning, Expertise, and Extension menus are the menus that take the longest time. The cause of errors in Expertise and Extension is due to the position of the menu that is difficult to see.